CULTURAL POLICY AND THE RISE OF MULTICULTURALISM STUDY OF FINE ARTS EXHIBITION IN THE 2000s, THE NATIONAL GALLERY OF INDONESIA - Dewi, Citra Smara (International Review of Humanities Studies, 2020)
This study focuses on the role of cultural policy in the rise of multiculturalism with a case study of the Indonesian Art Exhibition, Pameran Seni Rupa Nusantara (PSRN) 2000s, which was initiated by a cultural institution, the National Gallery of Indonesia (GNI). PSRN exhibition is one of the important programs of GNI because it gives space to the artists of the archipelago - not just Java and Bali - to present works of modern-contemporary art rooted in local wisdom. As a nation that has the characteristics of pluralism, the spirit of multiculturalism in art has become very significant, especially in the middle of the Disruption era which is "full of uncertainty". This article uses qualitative research with a historical method approach: heuristics, verification, interpretation and historiography, namely the process of writing history based on proven facts. Material Culture analysis approach, shows how history may be read and interpreted through objects/ artefacts/findings used by artists in their works. The results show that the Cultural Policy implemented by GNI is a combination of cultural policies that are authoritarian with the cultural policies of the Command, with an emphasis on the strength of the Potential Localization owned by the Indonesian people.